Síntese e caracterização de nanocompósitos magnéticos e sua aplicação na despoluição de águas - Mourão, Henrique Aparecido de Jesus Loures (2009)
The development of new materials should seek to products whose properties are integrated to enable that processes of interest are implemented efficiently. Thus, in the search for new heterogeneous catalysts, a challenge is integrate efficiently the catalytic activity with the ability to manipulate, separate and retain the structure from the reaction medium. Thus, this work proposed to the synthesis of catalysts based on semiconductors associated to ferrites, tailoring a nanocomposite. In order to obtain this, ferrites CoFe2O4 e Fe3O4 were synthesized through different methods. It was observed higher stability of the ferrite CoFe2O4 by the polymeric precursor method, while by the hydrolytic sol gel method only the ferrite Fe3O4 could be obtained. Following, TiO2-coated CoFe2O4 (TiO2/CoFe2O4) nanocomposites were synthesized in different weight proportions of CoFe2O4:TiO2 and also the SnO2/CoFe2O4 nanocomposites in the 56:44 weigh proportion, both by the polymeric precursor method. The nanocomposites TiO2/Fe3O4 and SnO2/Fe3O4 were synthesized by the hydrolytic sol gel method, in weigh proportion of 56:44 (Fe3O4:TiO2 or Fe3O4:SnO2). TiO2 nanocomposites showed surface area increase, due the higher surface roughness obtained by heterogeneous nucleation of TiO2 nanoparticles on ferrites surfaces. In SnO2 nanocomposites, the homogeneous nucleation of SnO2 nanoparticles also occurred. Also, it was observed higher photoactivity of the nanocomposites obtained by the polymeric precursor method due to the high crystallinity of these materials. The kinetic evaluation of the Rhodamine B photodegradation using the synthesized nanocomposites showed a pseudozero order reaction regarding to Rhodamine B. Finally, SnO2 nanocomposites (SnO2/CoFe2O4 e SnO2/Fe3O4) showed photocatalytic activity, being this result important since it was not reported yet in the literature.